2010
DOI: 10.1177/1082013210366750
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifying Properties of Chemically Deamidated Corn (Zea Mays) Gluten Meal

Abstract: Corn gluten meal is a by-product of starch production that is readily available. Corn protein isolates have limited applications due to their hydrophobic nature, low solubility and limited functionality as emulsifiers. In this study, a mild acidic treatment of corn gluten meal was performed in order to achieve deamidation of asparagine and glutamine residues and modify the interfacial behavior of this byproduct. A 0.1 N HCl treatment for 6 h at 70 °C rendered a deamidation degree of 20.4%, which increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The results in the present study are consistent with those of Motoki et al, working on glutamine-specific deamidation of α s1 -casein by transglutaminase, who found no changes in molecular weights. Similarly, Flores et al, working on maize protein isolate emulsions, found similar electrophoretic band patterns for deamidated and nondeamidated emulsions, despite their difference in emulsion stability. The fact that films prepared from transglutaminase-treated kafirin microparticles were rough (Figure Bn–p) may be attributed to an increase in negative charges in the kafirin due to deamidation, making the microparticles less soluble in acetic acid casting solution.…”
Section: Resultsmentioning
confidence: 80%
“…The results in the present study are consistent with those of Motoki et al, working on glutamine-specific deamidation of α s1 -casein by transglutaminase, who found no changes in molecular weights. Similarly, Flores et al, working on maize protein isolate emulsions, found similar electrophoretic band patterns for deamidated and nondeamidated emulsions, despite their difference in emulsion stability. The fact that films prepared from transglutaminase-treated kafirin microparticles were rough (Figure Bn–p) may be attributed to an increase in negative charges in the kafirin due to deamidation, making the microparticles less soluble in acetic acid casting solution.…”
Section: Resultsmentioning
confidence: 80%
“…In a similar but different experiment, Zhao, Tian, and Chen (2010) reported increased solubility, foaming capacity (FC), and ES of barley hordein at pH 3 to 7 compared to unmodified hordein. Flores, Cabra, Quirasco, Farres, and Galvez (2010) reported an increased emulsification activity index of corn gluten meal from 6.8 to 16.8 m 2 /g protein and ES from 0% to 90.6% oil retention for a 0.1 N HCl deamidation for 6 hr at 70°C. Most data on cereal protein deamidation showed the best improvements in functionality when the degree of deamidation was kept below 45% with a minimal (<3%) degree of hydrolysis (Cabra et al., 2007; Flores et al., 2010; Zhao et al., 2010).…”
Section: Modification Of Plant Proteins By Various Processing Techniquesmentioning
confidence: 97%
“…Flores, Cabra, Quirasco, Farres, and Galvez (2010) reported an increased emulsification activity index of corn gluten meal from 6.8 to 16.8 m 2 /g protein and ES from 0% to 90.6% oil retention for a 0.1 N HCl deamidation for 6 hr at 70°C. Most data on cereal protein deamidation showed the best improvements in functionality when the degree of deamidation was kept below 45% with a minimal (<3%) degree of hydrolysis (Cabra et al., 2007; Flores et al., 2010; Zhao et al., 2010). However, an increase in solubility, EAI, ESI, and foamability but a decrease in FS were recorded for up to 72.1% degree of deamidation when soymilk residue protein was deamidated at 65 °C for 48 hr using 0.01 to 0.3 N HCl (Chan & Ma, 1999).…”
Section: Modification Of Plant Proteins By Various Processing Techniquesmentioning
confidence: 97%
“…Most previous researches have been done on chemical deamidation of proteins from wheat, corn, barley, and soy, but not from pulses. These previous data suggest that favorable functionality can achieve by controlled deamidation level < 45% from cereal proteins and 72% from soy proteins 42‐45 …”
Section: Modification Methods Of Pulse Protein Ingredientsmentioning
confidence: 86%
“…These previous data suggest that favorable functionality can achieve by controlled deamidation level < 45% from cereal proteins and 72% from soy proteins. [42][43][44][45] Glycosylation involves the attachment of carbohydrate moieties to the amino acid side chain lysine residues or the N-terminus of a protein. This reaction usually occurs during the Maillard reaction.…”
Section: Chemical Modificationmentioning
confidence: 99%